2015
DOI: 10.1002/brb3.375
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructure between the pre‐SMA and the cingulum bundle is related to response conflict in healthy subjects

Abstract: IntroductionResponse conflict involves selectively attending to relevant information and suppressing distracting, irrelevant information. The medial frontal cortex (MFC) is considered to be involved in response conflict. However, it remains unclear which white matter connectivity is associated with response conflict. This study aimed to delineate the neural connectivity of response conflict in healthy subjects and investigate the association between white matter microstructure and performance of a response con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
(138 reference statements)
1
5
0
Order By: Relevance
“…In line with these findings, resting state functional connectivity data found pre-SMA to be linked to cognitive processing regions whereas SMA proper exhibited stronger connectivity to motor cortex (Wang et al 2013). Furthermore, pre-SMA shows white matter connectivity to the cingulate cortex via the cingular bundle, which seems to be functionally associated to the processing of response conflicts (Yamamoto et al, 2015). A study on connectivity between basal ganglia and cortical regions during the performance of speech tasks found differential patterns with regard to linked to regions involved in cognitive linguistic processes (pre-SMA, dorsal anterior insula, and inferior frontal gyrus) whereas GPi showed stronger connectivity to regions involved in motor control (middle insula, SMA proper, premotor cortex) (Manes et al, 2014).…”
Section: Anatomy and Connectivitysupporting
confidence: 57%
“…In line with these findings, resting state functional connectivity data found pre-SMA to be linked to cognitive processing regions whereas SMA proper exhibited stronger connectivity to motor cortex (Wang et al 2013). Furthermore, pre-SMA shows white matter connectivity to the cingulate cortex via the cingular bundle, which seems to be functionally associated to the processing of response conflicts (Yamamoto et al, 2015). A study on connectivity between basal ganglia and cortical regions during the performance of speech tasks found differential patterns with regard to linked to regions involved in cognitive linguistic processes (pre-SMA, dorsal anterior insula, and inferior frontal gyrus) whereas GPi showed stronger connectivity to regions involved in motor control (middle insula, SMA proper, premotor cortex) (Manes et al, 2014).…”
Section: Anatomy and Connectivitysupporting
confidence: 57%
“…Stroop performance, particularly in the context of positive distractors (Keedwell et al, 2016), has been associated with CB integrity, indicating the functional consequences of these white matter decrements. Other studies have observed that CB integrity is linked to performance on tasks of response conflict and sustained attention (Takahashi et al, 2010; Yamamoto et al, 2015). Injury to this path has been linked to deficits on tasks of executive control e.g., (Cohen et al, 1999; Janer and Pardo, 1991; Kim et al, 2003), and reduced emotional responsivity (Cohen et al, 2001).…”
Section: Discussionmentioning
confidence: 95%
“…In addition to connecting fronto-parietal control network areas, the limbic aspects of this tract access emotion processing regions. Integrity of the CB has been associated with performance on cognitive control/response inhibition tasks in healthy (Takahashi et al, 2010; Yamamoto et al, 2015) and psychiatric populations (Keedwell et al, 2016; Takei et al, 2009). Stroop performance, particularly in the context of positive distractors (Keedwell et al, 2016), has been associated with CB integrity, indicating the functional consequences of these white matter decrements.…”
Section: Discussionmentioning
confidence: 99%
“…This proposition can be supported by some functional studies. For example, white matter connectivity between the pre-SMA and the CB was associated with response conflict in healthy human subjects (Yamamoto et al, 2015 ). Huang et al ( 2013 , 2014 ) also found that the microstructural integrity of the white matter connecting the anterior cingulate area to the precuneus and medial superior frontal areas reflected the level of neurophysiologic dependence in tobacco withdrawal syndrome.…”
Section: Discussionmentioning
confidence: 99%